PENGARUH KEPEMIMPINAN, KEMAMPUAN, DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN INDRAGIRI HULU - Mahdalena S; Woro Utari (MAP (Jurnal Manajemen dan Administrasi Publik), 2018)
This study aims to mengatahui and describe the variables of leadership conditions, abilities, work discipline and performance of employees of the Office of Education and Culture Indragiri Hulu regency. In addition to mengatahui and discuss the variables of leadership, ability and work discipline partially or simultaneously have a significant effect on the performance of employees of Education and Culture Office of Indragiri Hulu Regency. This research is an explanatory research with quantitative descriptive approach. The population of this study as many as 66 people. The sample of research used in Education and Culture Office of Indragiri Hulu Regency is 65 people. The data analysis technique is a multiple linear regression. The results show leadership, ability and discipline both partially and simultaneously have a significant influence on the performance of employees of the Department of Education and Culture Indragiri upstream regency. Keywords: leadership, ability, work discipline and performance